2007
DOI: 10.1007/s00464-006-9097-4
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis in the elderly: a change in the laparoscopic era

Abstract: Minimally invasive surgery combined with increased use and accuracy of preoperative CT scans has changed the clinical management of acute appendicitis in elderly patients, leading to decreased lengths of stay, decreased mortality, and more favorable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 14 publications
(24 reference statements)
0
27
2
3
Order By: Relevance
“…Our operation time (57.98 minutes) was found to be shorter than most of the literature findings (78.3-88 minutes) (20,21,26). This was a result of lower laparoscopic appendectomy rates (6.6% only) of our study.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Our operation time (57.98 minutes) was found to be shorter than most of the literature findings (78.3-88 minutes) (20,21,26). This was a result of lower laparoscopic appendectomy rates (6.6% only) of our study.…”
Section: Discussioncontrasting
confidence: 58%
“…This was a result of lower laparoscopic appendectomy rates (6.6% only) of our study. The mean length of hospital stay was found only 3.89 days that is also shorter than recent studies (20,21,26). We found that perforation of the appendix increases mortality rates and complications.…”
Section: Discussioncontrasting
confidence: 52%
“…Aufgrund von Komorbiditäten muss von einer signifikant erhöhten Morbidität und Letalität ausgegangen werden [7,9,22]. Gassel et al beschreiben eine 2,5fach erhöhte Morbidität und eine 12fach erhöhte Letalität im Rahmen der akuten Appendizitis bei Patienten über 50 Jahre [9].…”
Section: Tab 3 Appendektomie-komplikationen In Den Verschiedenen Altunclassified
“…Auch für Patienten mit Perforation ist die Laparoskopie mittlerweile die Methode der Wahl [15,20]. Für ältere Patienten zeigen derzeit mehrere Studien Vorteile der laparoskopischen gegenüber der konventionellen oder offenen Appendektomie [7,12,22,24]. So beschreiben Paranjape et al durch minimal-invasive Therapie der akuten Appendizitis bei älteren Patienten eine verringerte Morbidität und kürzere Liegezeiten [22].…”
unclassified
“…It should also be noted that the rates of perforation are much higher in the elderly population and so many of the patients can also present with diffuse abdominal tenderness and peritonism (Korner et al, 1997;Hiu et al, 2002). The differential diagnosis for elderly patients presenting with abdominal pain is much broader and therefore when such a patient presents, especially with a non specific history, a computed tomography scan is the imaging modality of choice (Paranjape et al, 2007). In such circumstances, the presence of any other pathology can be assessed with a computed tomography scan and the appropriate management can be planned accordingly.…”
Section: Appendicitis At the Extremes Of Agementioning
confidence: 99%